Atendimento escolar hospitalar no contexto da pandemia COVID-19: enfrentamentos vividos na prática pedagógica - Sampaio, Jin Kyong Karina (Universidade Federal de São Carlos, 2022)
The present research, of a qualitative nature, sought to dialogue with teachers of hospital classes and authors of hospital pedagogy field, previously carrying out a search for information through the literature and the exploratory study from a survey, all remotely, due to the research being carried out during the COVID-19 pandemic period. The ultimate goal was to research briefly about Hospital Pedagogy, its definition, fundamentals laws and its importance to society. I related my study of this area of pedagogy with the current situation in Brazil, and in the world, due to the COVID-19 pandemic, observing, commenting and analyzing how hospital school attendance are working during the pandemic, their pedagogical practice. With this research, I will contribute to the study of hospital pedagogy field, which is still relatively scarce, and also to research on COVID-19, which is a very current and extremely important topic. I tried to understand what were the difficulties, the challenges faced by the pedagogues of the hospital school attendance and how they did to solve or to overcome these problems. In the first chapter I bring the introduction of the research, in the second and third chapters there is the theoretical foundation of the research. In chapter II, being divided into three topics, I bring a brief hospital pedagogy history in Brazil and in the world, the role of professionals in hospital school attendance, and pedagogical practice and its environment. In chapter III I discuss the COVID19 pandemic, a bit about the general educational system in this context and about hospital school attendance. The approach and procedures of this research are found in chapter IV. In chapter V, an analysis of the teachers' answers to the survey is presented, followed by a reflection and dialogue, based on the authors used in the theoretical foundation, everything being divided into six topics and two subtopics. It was possible to conclude (chapter VI) that in Brazil, teaching practice differed a lot between 2020 and 2021, each institution approached a different way of continuing with teaching practice in hospitals, trying to maintain a teachinglearning process that could reached the students.
Hospital school attendance in the context of the COVID-19 pandemic: encounters experienced in pedagogical practice
Keywords: ambiente escolar hospitalar; pedagogia hospitalar; pandemia COVID 19; Hospital School Attendance; Hospital pedagogy; Pandemic COVID-19; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO